MicroRNA Profiling in Chronic Limb-Threatening Ischemia Their Role in Arteriogenesis - Ismail, Muhamad T.; Setianto, Budi Y.; Haryana, Sofia M.; Anggrahini, Dyah W. (International Journal of Angiology, 2025)
Chronic limb-threatening ischemia (CLTI) represents poses a substantial threat with escalating mortality and amputation rates. Despite the existence of various clinical techniques for diagnosing CLTI, the role of microRNAs (miRNAs) in arteriogenesis remains ambiguous. Comprehensive knowledge on miRNAs may facilitate the advancement of targeted therapy pertaining to the enhancement of collateral blood flow in obstructed vessels. Therefore, this study aimed at analyzing arteriogenesis-associated plasma miRNA profiles in patients with CLTI using gene expression. Samples were acquired from the collateral arteries (CA group, n = 3) and the contralateral healthy limb (healthy artery; HA group, n = 3) of a single set of patients with CLTI. The RNA extracted from the samples was assessed for concentration and purity. A normalization factor was used to address variations in analyte abundance and/or quality across the samples. Subsequently, individual RNA molecules were directly quantified and subjected to comparative analysis between the CA and HA groups to identify the miRNAs involved in arteriogenesis. The five arteriogenesis-related miRNAs exhibiting maximum upregulation were miR-301b–3p, miR-221–5p, miR–639, miR-34a–5p, and let-7a–5p, while the five most downregulated miRNAs included miR-151a–5p, miR-371a–5p, miR-651–5p, miR-510–5p, and miR-660–5p. Summarily, this study documented marked upregulation and downregulation of miRNAs associated with arteriogenesis in the collateral arteries of patients with CLTI as compared with their contralateral healthy limbs. Possible mechanisms involved, including the regulation of YAP/TAZ pathway, TGFBR3 mRNA, SIRT1 expression, and other processes have shown to be modulated by miRNAs fluctuations.
Keywords: chronic limb-threatening ischemia; microRNA; sequencing; arteriogenesis; YAP/TAZ pathway; TGFBR3 mRNA; SIRT1 expression